2002
DOI: 10.1016/s0002-9440(10)64465-3
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Inhibits Phosphorylation and Autonomous Activity of Ca2+/Calmodulin-Dependent Protein Kinase II in Vascular Smooth Muscle Cells

Abstract: Vascular smooth muscle cell (VSMC) hyperproliferation is a characteristic feature of both atherosclerosis and restenosis seen after vascular surgery. A number of studies have shown that heparin inhibits VSMC proliferation in vivo and in culture. To test our hypothesis that heparin mediates its antiproliferative effect by altering Ca 2؉ regulated pathways involved in mitogenic signaling in VSMC, we analyzed the effect of heparin on multifunctional Ca 2؉ /calmodulin dependent protein kinase II (CaM kinase II) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 50 publications
(67 reference statements)
3
19
0
Order By: Relevance
“…Mori et al (34) suggested that histidine-rich glycoprotein, in combination with the zinc ion, plays a role in modulating the SMC growth response in pathophysiological states and explains the lack of success of heparin as a therapeutic antirestenosis drug in clinical trials. Mishra-Gorur et al (35) showed that alterations in calcium-mediated mitogenic signalling pathways may be involved in the antiproliferative mechanism of action of heparin. He et al (36) showed that a heparinoid at 1.6 mg/mL to 0.05 mg/mL significantly inhibits VSMC proliferation induced by FCS (10%), basic fibroblast growth factor or interleukin-1.…”
Section: Discussionmentioning
confidence: 99%
“…Mori et al (34) suggested that histidine-rich glycoprotein, in combination with the zinc ion, plays a role in modulating the SMC growth response in pathophysiological states and explains the lack of success of heparin as a therapeutic antirestenosis drug in clinical trials. Mishra-Gorur et al (35) showed that alterations in calcium-mediated mitogenic signalling pathways may be involved in the antiproliferative mechanism of action of heparin. He et al (36) showed that a heparinoid at 1.6 mg/mL to 0.05 mg/mL significantly inhibits VSMC proliferation induced by FCS (10%), basic fibroblast growth factor or interleukin-1.…”
Section: Discussionmentioning
confidence: 99%
“…miR-145 represses Klf4, which otherwise interacts with SRF and also represses myocardin, 40 and calmodulin kinase II-␦ (CamkII-␦), which was shown to be involved in multiple events including neointimal proliferation. 41,42 miR-143 represses Elk-1 (Ets LiKe gene 1), which competes with myocardin to bind SRF and exhibits an inhibitory effect on smooth muscle differentiation. 43 Klf4 plays a key role in regulating VSMC phenotype because it antagonizes proliferation, facilitates migration, and downregulates VSMC differentiation marker genes.…”
Section: Mir-143/145 Regulation Of Vsmc Proliferation and Differentiamentioning
confidence: 99%
“…MAPK cascade has also shown to be required for p27 kip1 down-regulation and S phase entry in fibroblasts and epithelial cells (80). Inhibitory effects of heparin on activation of calmodulin-dependent protein kinase II have been documented by Mishra-Gorur et al (81,82) in VSMC. Recently, it has been shown that inhibition of calmodulindependent protein kinase II in NIH 3T3 cells enhances association of p27 kip1 with Cdk2 and thus causes a G 1 arrest (83).…”
Section: Fig 5 Heparin Treatment Of Vsmc Increases the Half-life Ofmentioning
confidence: 93%